Desenvolvimento das fundações para acessibilidade em Ambiente pré-OS - Machado, Rafael Rodrigues (2018)
People with some kind of disability face a high level of difficulty for everyday tasks. This difficulty is due solely to the fact that in many cases accessibility was not considered necessary when the task was created. An example of this scenario is the BIOS configuration of computers, which do not present any option that considers the existence of people with some more specific need, such as screen readers in the case of visual impairement. Focusing on this need, this work validates that it is possible to make the pre-operating system’s environment accessible to visually impaired people by developing the audio support in this environment, to be executed on systems that have BIOS compatible with the UEFI specification, and audio cards compatible with the High Definition Audio specification. As a result, a proof of concept for the operation of audio cards in a pre-OS environment has been made available to the community. With the existence of this code base it is believed that it will be possible for those responsible for the UEFI specification to start discussions related to creating the abstraction for multimedia devices.